BIOGRAPHICAL OBSESSION OF JIMMY PORTER IN LOOK BACK IN ANGER - Memet Metin BARLIK (Fırat University, 2019)
Look Back in Anger (1956) reflects the life expectancies of working class in postwar England, questioning the political attitude of ruling class. Jimmy Porter is a keen spokesman character to defend the ‘anger' of lower middle class but fails to escape revealing the ‘anger' of his biographical background. He discusses the reasons for social inertia but is a loser of relative deprivation in his private life. Jimmy has a self-sacrificing role in his leadership to awake and make the i